Trade-offs between visual and chemical behavioral responses - Martins, Emilia P. (2018)
Multiple and multimodal signals can evolve because they convey different information to different receivers or in different contexts. From the perspective of display receivers, however, multimodal signals may pose a challenge since evolutionary changes in any one aspect of the signal may require shifts in other aspects of receiver physiology and behavior. Here, we use field experiments with four species of Sceloporus lizards to test whether evolutionary loss of one element of a complex signal (a colorful belly patch) has led to a change in the behavioral response to a live conspecific. Instead, we found that males of three species (S. merriami, cozumelae, and siniferus) responded to the live conspecific with increased visual and decreased chemical behavior, supporting a Sensory Isolation hypothesis in which animals minimize interference by isolating a single sensory modality, for example, closing eyes to pay closer attention to a sound or smell. In an exception that offers additional support, males of the fourth species, S. parvus, also showed a trade-off in their response, but responded to the live stimulus with more chemical and less visual behavior. We found little evidence that lizards that have lost production of one signal element (belly color) have also altered their response behavior as a consequence. These results emphasize the potentially important role of receiver response in maintaining complex and multimodal signals.